Early Diagnosis and Lung Cancer Screening. Issue 11 (November 2022) - Balata, H.; Quaife, S.L.; Craig, C.; Ryan, D.J.; Bradley, P.; Crosbie, P.A.J.; Murray, R.L.; Evison, M.
Abstract: Lung cancer remains the most significant cause of cancer death, accounting for about 20% of all cancer-related mortality. A significant reason for this is delayed diagnosis, either due to lack of symptoms in early-stage disease or presentation with non-specific symptoms common with a broad range of alternative diagnoses. More is needed in terms of increasing public awareness, providing adequate healthcare professional education and implementing clinical pathways that improve the earlier diagnosis of symptomatic lung cancer. Low-dose computed tomography screening of high-risk, asymptomatic populations has been shown to reduce lung cancer mortality, with focus now shifting towards how best to implement lung cancer screening on a wider scale in a safe, efficient and cost-effective manner. For maximum benefit, efforts must be made to optimise uptake, especially among high-risk populations with significant socioeconomic deprivation, as well as successfully incorporate tobacco-dependency treatment. Quality assured programme management will be critical to minimising screening-related harms and adequately managing incidental findings. By undertaking the above, there can be optimism that lung cancer outcomes can be improved significantly in the near future.